Psychosis effect on hippocampal reduction in schizophrenia - Hýža, Martin; Huttlová, Jitka; Keřkovský, Miloš; Kašpárek, Tomáš (Progress in neuro-psychopharmacology & biological psychiatry, 2014)
INTRODUCTION: In schizophrenia, disruption of the neurodevelopmental processes may lead to brain changes and subsequent clinical manifestations of the illness. Reports of the progressive nature of these morphological brain changes raise questions about their causes. The possible toxic effects of repeated stressful psychotic episodes may contribute to the disease progression. OBJECTIVES: To analyze the influence of illness duration and previous psychotic episodes on hippocampal gray matter volume (GMV) in schizophrenia. METHODS: We performed an analysis of hippocampal GMV correlations with illness duration, number of previous psychotic episodes, and age in 24 schizophrenia patients and 24 matched healthy controls. RESULTS: We found a cluster of GMV voxels in the left hippocampal tail that negatively correlated with the number of previous psychotic episodes, independent from the effect of age. On the other hand we found no effect of illness duration independent of age on the hippocampal GMV. Finally, we found a cluster of significant group-by-age interaction in the left hippocampal head. CONCLUSIONS: We found an additive adverse effect of psychotic episodes on hippocampal morphology in schizophrenia. Our findings support toxicity of psychosis concept, together with etiological heterogeneity of brain changes in schizophrenia.
Keywords: SPM; Magnetic Resonance Imaging; SD; magnetická rezonanční tomografie; Humans; VBM; Case-Control Studies; Functional Laterality; AAL; GLM; MRI; vesicular glutamate transporter 1; BDNF; serotonine-dopamine antagonists; general linear model; studie případů a kontrol; automatic anatomical labeling; schizofrenie; Female; mladý dospělý; dospělí; brain-derived neurotrophic factor; gamma-amino butyric acid; věkové faktory; Psychiatric Status Rating Scales; WFU; Hippocampus; VGLUT1; GMV; lidé; multi-acting receptor-targeted antipsychotics; Schizophrenia; FWE; Psychosis; magnetic resonance imaging; psychotické poruchy; hipokampus; počítačové zpracování obrazu; family-wise errors; Image Processing, Computer-Assisted; Toxicity; gray matter volume; AMPA; standard deviation; FDR; dentate gyrus; Adult; NMDA; ženské pohlaví; N-methyl D-aspartate; funkční lateralita; psychiatrické posuzovací škály; Male; Morphometry; Wake-Forrest University; statistical parametrical mapping; CA; cornu ammonis; MARTA; voxel-based morphometry; α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid; Young Adult; GABA; Age Factors; mužské pohlaví; Psychotic Disorders; HPA; SDA; false discovery rate; DG; hypothalamo-pituitary axis